Dermoscopy comparative approach for early diagnosis in familial melanoma: influence of MC1R genotype. (28th July 2020) - Longo, C.; Barquet, V.; Hernandez, E.; Marghoob, A.A.; Potrony, M.; Carrera, C.; Aguilera, P.; Badenas, C.; Malvehy, J.; Puig, S.
Abstract: Background: MC1R polymorphisms interact with CDKN2A mutations modulating melanoma risk and contribute to a less suspicious clinical and dermoscopic appearance of melanomas. Different strategies, including dermoscopic comparative approach and digital monitoring, are used for the melanoma diagnosis in this context. Objective: To analyse the diagnostic accuracy of the morphologic approach and comparative approach in dermoscopy, and to detect melanoma in familial melanoma (FamMM) patients according to different genetic backgrounds. Methods: Two independent readers evaluated 415 lesions belonging to 25 FamMM: 26 melanomas (62% in situ, 36% early invasive) and 389 naevi, blinded for dermoscopic and histopathologic diagnosis, following two different steps. First step‐ Randomized : all lesions were randomly located in one single folder. Second step‐ Comparative approach : the lesions were clustered by patient. Sensitivity, specificity and number needed to excise (NNE) for melanoma diagnosis were calculated for both diagnostic strategies. Sensitivity and specificity were also assessed regarding the genetic background. Results: The comparative approach showed lower sensitivity compared to the morphologic approach (69.2 and 73.1 vs. 76.9 both readers) but better specificity (95.9 and 95.1 vs. 84.3 and 90.2, respectively). NNE was better in the comparative approach. The readers had more difficulties diagnosing lesions from CDKN2A mutation carriers with red hair colour (RHC) MC1R variants. Conclusion: The comparative approach can be useful in high‐risk patients to decrease the NNE. Early melanomas in CDKN2A carriers with RHC polymorphisms are more difficult to diagnose even with the comparative approach and benefit from the detection of changes during digital dermoscopy monitoring for early diagnosis. Abstract : Linked Commentary: A. Lallas. J Eur Acad Dermatol Venereol 2021; 35: 274‐275. https://doi.org/10.1111/jdv.17104 .